Pengaruh Bahan Tambahan pada Kualitas Kompos Kotoran Sapi - Ni Made Eva Yulia Dewi (Jurnal BETA (Biosistem dan Teknik Pertanian), 2017)
The used of additional materials in the composting process of cow manure feedstock can produced qualified compost that can fulfill standard of compost. This study used the treatment of exponential design cow manure, cow manure:saw dust 2:1, cow manure:rice hull 2:1, and cow manure:elephant grass 2:1. The dimension of pile composting was 1.5 m, with height was 80 cm, and 1 m of width. The observed parameters included temperature, pH, carbon and nitrogen compost. The composting process were during eight weeks that result which have temperature between 25-51oC , compost pH between 6.6-7.0, C/N ratio is 16.8-20.93. The color of produced compost was dark brown. The quality of the produced compost from the four treatments were accordance to SNI Standard 19-7030-2004.